ApoA-I Infusions and Burden of Ischemic Events After Acute Myocardial Infarction: Insights From the AEGIS-II Trial - Gibson, C Michael; Chi, Gerald; Duffy, Danielle; Bahit, M Cecilia; White, Harvey; Korjian, Serge; Alexander, John H; Lincoff, A Michael; Anschuetz, Gaya; Girgis, Ihab G; Nicolau, Jose C; Lopes, Renato D; et al. (Journal of the American College of Cardiology, 2024)
Following an acute myocardial infarction (AMI), patients remain at risk for subsequent cardiovascular (CV) events. In the AEGIS-II trial, CSL112, a human apolipoprotein A-I derived from plasma that enhances cholesterol efflux, did not significantly reduce the first occurrence of CV death, myocardial infarction (MI), or stroke through 90 days compared with placebo. However, an analysis involving only the first event may not capture the totality of the clinical impact of an intervention because patients may experience multiple events. This prespecified exploratory analysis examines the effect of CSL112 on total burden of nonfatal ischemic events (ie, recurrent MI and stroke) and CV death. A total of 18,219 patients with AMI, multivessel coronary artery disease, and additional CV risk factors were randomized to either 4 weekly infusions of 6 g CSL112 (n = 9,112) or matching placebo (n = 9,107). A negative binomial regression model was applied to estimate the effect of CSL112 compared with placebo on the rate ratio (RR) of ischemic events. For CV death, MI, and stroke, there were numerically fewer total events at 90 days (503 vs 545 events; rate ratio [RR]: 0.88; 95% CI: 0.76-1.03, P = 0.11), and nominally significantly fewer total events at 180 days (745 vs 821 events, RR: 0.87; 95% CI: 0.77-0.99; P = 0.04) and 365 days (1,120 vs 1,211 events; RR: 0.89; 95% CI: 0.80-0.99; P = 0.04). Subsequent events constituted 13% of events at 90 days, 17% at 180 days, and 22% at 1 year. Similar findings were seen with the total occurrence of nonfatal MI and CV death. When type II MIs, unlikely to be modified by enhancing cholesterol efflux, were excluded, there were nominally significant reductions in the total occurrence of nonfatal MI (excluding type 2) and CV death at all time points (90 days: RR: 0.81; 95% CI: 0.68-0.97; P = 0.02; 180 days: RR: 0.82; 95% CI: 0.71-0.95; P < 0.01; 365 days: RR: 0.86; 95% CI: 0.76-0.98; P = 0.02). In this prespecified exploratory analysis of the AEGIS-II trial, 4 weekly infusions of CSL112 among high-risk patients after AMI significantly reduced the total burden of nonfatal ischemic events and CV death at 180 and 365 days compared with placebo. (AEGIS-II [Study to Investigate CSL112 in Subjects With Acute Coronary Syndrome]; NCT03473223).